Analysis of Tourism Product Innovation and Viral Marketing on Tourist Visiting Decisions in The New Normal Era Through Tourism Image in Bangli District - Made Mulia Handayani; Nyoman Dwika Ayu Amrita; Made Ayu Desy Geriadi; Luh Erynayati; I Made Kartika (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Since the Covid-19 pandemic there has been a decline in the number of tourists to Bangli district, it is necessary to make an innovation so that the world of tourism in Bangli district can continue to develop. This study aims to determine the effect of tourism product innovation on tourism image, to determine the effect of viral marketing on tourism image, to determine the effect of tourism product innovation on visiting decisions, to determine the effect of viral marketing on visiting decisions and to determine the effect of tourism images on visiting decisions. The sample in this study amounted to 96 tourists. This study uses Structural Equation Modeling (SEM) with a variance based or component based approach with Partial Least Square (PLS). The results in this study prove that tourism product innovation has a positive and significant effect on tourism image, viral marketing has a positive and significant effect on tourism image, product innovation has a positive and significant effect on visiting decisions, viral marketing has a positive and significant effect on visiting decisions, and tourism image. has a positive and significant effect on visiting decisions.